DEVELOPING A CRISIS MANAGEMENT MODEL FOR SHARIA BANKING BASED ON ISLAMIC JURISPRUDENCE - Siti Mahmudah; Ahmed Al Fahad; Fatimah Al Rashid (Yayasan Adra Karima Hubbi, 2026)
Increasing uncertainty in the global financial environment has intensified the need for effective crisis management frameworks capable of strengthening institutional resilience and ensuring sustainable organizational performance. Sharia banking institutions face unique challenges during crises because operational decisions must comply not only with regulatory requirements but also with Islamic legal and ethical principles. Existing crisis management models are predominantly derived from conventional management theories and often provide limited guidance regarding the integration of Islamic jurisprudential principles into crisis preparedness, response, and recovery processes. This study aims to develop and validate a crisis management model for Sharia banking institutions based on Islamic jurisprudence. A mixed-methods research design was employed using an exploratory sequential approach. Qualitative data were obtained through expert interviews and analysis of Islamic jurisprudential sources, while quantitative data were collected from 320 professionals working in Islamic banking institutions. Structural Equation Modeling was utilized to evaluate the proposed framework. Findings reveal that Sharia compliance governance significantly enhances crisis preparedness, ethical decision-making, stakeholder protection, organizational resilience, and recovery capacity. Ethical decision-making emerged as a critical mediating factor linking jurisprudential principles to resilience outcomes. Results further indicate that concepts such as maslahah, darurah, amanah, and harm prevention provide practical guidance for crisis management within Islamic banking contexts. The study concludes that Islamic jurisprudence offers a comprehensive foundation for developing resilient, ethical, and stakeholder-oriented crisis management systems capable of strengthening governance quality and long-term institutional sustainability in Sharia banking.